Improcedencia del inciso final del articulo 581 del código orgánico integral penal, por contraponerse a la potestad del fiscal de iniciar la investigación de oficio en los delitos de acción pública - Delgado Guachichulca, Jairo Rene (2016)
The present research paper whose theme is "IMPROCEDENCE OF THE FINAL STATEMENT OF ARTICLE 581 THE CODE COMPREHENSIVE CRIMINAL ORGANIZATION, FOR COUNTERING THE FISCAL'S POTESTY OF INITIATING THE INVESTIGATION OF OFFICE IN THE CRIMES OF PUBLIC ACTION" is thus the objective of this Work of Investigation is oriented to the legal and critical analysis of the procedures and claims in the application of the functions of the Office of the Attorney General, as well as to establish a legal reform to the Integral Criminal Code, for addressing an issue of the juridical and social reality of Ecuador. The Constitution of the Republic defines the public administration as: "a service to the community that is governed by the principles of effectiveness, efficiency, quality, hierarchy, deconcentration, decentralization, coordination, participation, planning, transparency and evaluation." Public administration, then, is one of the specific manifestations of the power of the State, which has the power to impose its will, which is called Jus Imperium, all based on the public interest. To this end, it is endowed with autonomy and administrative autonomy which is the power to act that the administration has without the necessary intervention of an impartial third party, which gives certainty and legal value of executive and executory title to the manifestations of its will. Therefore, the mission of the Office of the Prosecutor is the social representation that acts in defense of the public interest, of the people and for the citizen security, ensuring the correct application of the law, but as I will show later, subject to the principles of Opportunity, minimal penal intervention and objectivity. Thus, the final paragraph of article 581 of the Integrated Code of Criminal Procedure establishes a procedure budget for the initiation of the investigation, only for crimes of embezzlement and illicit enrichment, there must be a previous report with indications of criminal responsibility issued exclusively by The Public Prosecutor, which is clearly an obstacle to the institution of this institution can directly exercise its powers conferred by the Constitution and laws, and initiate ex officio an investigation when it comes to its knowledge the alleged involvement of one Of these crimes, which undoubtedly generates impunity and insecurity, since most of these crimes are not being investigated, let alone tried, with the agility and efficiency with which these violations merit since they are against the interest of the State, since That the criterion of the prosecutor should be the same for a matter that of course was followed.